KETERLAKSANAAN KURIKULUM 2013 UNTUK MELATIH KEMAMPUAN BERPIKIR KRITIS SISWA PADA MASA PEMBELAJARAN ONLINE PANDEMI COVID-19 - Wiryanto, Wiryanto; Ainurrohmah, Indah; Yasin, Fajar Nur (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2021)
The background of the research is to analyze the critical thinking skills of fourth grade elementary school students. The ability to think critically is one of the important things in the 2013 curriculum. Teachers as facilitators must be able to train students’ critical thinking skills even though learning during the pandemic does not run normally. This study seeks to train students’ critical thinking skills by presenting learning tools with an open-ended approach. This approach stimulates student activity and creativity in problem solving so that it is considered to be able to train students’ critical thinking skills. This research was conducted using the Pre-Experimental Design method in the form of One-Group Pretest-Posttest Design. The procedure of this research is to carry out a pretest before being given learning treatment and implementing a posttest after being given a learning treatment with an open-ended approach. Sources of data in this study were grade IV elementary school students totaling 23 students